2016
DOI: 10.1007/s00484-016-1191-2
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and lactation responses of Egyptian dairy Baladi goats to natural thermal stress under subtropical environmental conditions

Abstract: The objective of this study was to evaluate the impact of thermal stress on milk production and physiological traits of Baladi goats under subtropical Egyptian conditions. Sixty dairy Baladi goats were exposed to three different levels of temperature-humidity index (THI), including low (less than 70), moderate (over 70 and up to 80), and high levels (over 80). The influence of THI on the milk composition and physiological, hematological, and biochemical traits was investigated. Rectal temperature and respirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…In recent years, interest in commercializing goat milk production for human consumption and cheese manufacture is attracting producers due to growing demand (Mestawet et al, 2012, El-Tarabany et al, 2016). In the current study, the average daily-MY in Baladi goats was comparable to former trials, where the peak was attained at the early stage of lactation, and then a steady decline was observed thereafter until the end of lactation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, interest in commercializing goat milk production for human consumption and cheese manufacture is attracting producers due to growing demand (Mestawet et al, 2012, El-Tarabany et al, 2016). In the current study, the average daily-MY in Baladi goats was comparable to former trials, where the peak was attained at the early stage of lactation, and then a steady decline was observed thereafter until the end of lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Sevi et al (2001) have reported that the provision of shade helped minimizing the impact of thermal stress in the immune function and udder health of ewes. High environmental temperatures can lead to reduced leucocyte counts in sheep (El-Tarabany, El-Tarabany, & Atta, 2017). Also, in such cases, leucocytes have impaired function (e.g.…”
Section: Climatological Factorsmentioning
confidence: 99%
“…Among the environmental variables affecting animals, heat stress is one of the factors making animal production challenging in many parts of the world (El-Tarabany et al, 2017).…”
Section: Introductionmentioning
confidence: 99%